Chaotic photon spheres in non-Euclidean billiard - Wang Dongyang; Liu Changxu; Zhang Shuang; Chan Che Ting (Nanophotonics, 2020)
With the advancement in understanding of the physics inside chaotic systems, chaos has been harnessed from a nuisance to a beneficial factor in optical devices. Light–matter interaction in chaotic systems has been utilised for improving broadband energy harvesting and momentum transformations, achieving light localization beyond diffraction limit and even stabilizing the dynamics of high power laser. While extensive study about wave chaos has been made in deformed microcavities, investigation of how chaos dynamics evolves in curved space manifold remains elusive. Here, we study the non-Euclidean billiard of a torus-like manifold, which is a closed 2D cavity system with effective periodic boundaries. The ray chaotic behaviours on the deformed toroidal surface are explored using the geodesic equation. By tuning the deformation parameter of the torus, we observe the transition of the billiard from the ordered phase state to mixed phase states and then complete ray chaos. The photon sphere of the torus is identified as the transition position from ordered states to chaotic states. Compared with other chaotic behaviours resulted from the random scattering inside deformed cavities, we demonstrate chaotic dynamics purely on a curved surface, which may shed light on the better understanding of chaos in optics.